Antibacterial potential of biosynthesized silver nanoparticles using Nepeta sessilifolia Bunge and Salvia hydrangea DC. ex Benth. extracts from the natural habitats of Iran's Rangelands - Mansureh Ghavam (BMC, 2023)
Abstract Background Nowadays, the use of herbal extracts for the production of nanoparticles has attracted a lot of attention due to the fast reaction, economy, and compatibility with the environment. The aim of the present study is the biosynthesis of silver nanoparticles from the extracts of Nepeta sessilifolia Bunge and Salvia hydrangea DC. ex Benth. and their antibacterial activity was measured. Methods For this purpose, the flowering branch of N. sessilifolia and the flower of S. hydrangea were randomly collected from three places, respectively, from the rangelands of Aqdash Mountain and Biabe in Isfahan province, Iran in May 2021. After extracting aqueous extracts by hot method, silver nanoparticles were synthesized by the biological method. Green synthesized silver nanoparticles were analyzed by UV-Vis spectroscopy, XRD, FTIR, and FESEM-EDAX. The antibacterial effect was evaluated by diffusion method in agar and determination of minimum growth inhibitory and lethal concentration (MIC and MBC) by dilution method in liquid culture medium. Results Based on the results of UV-Vis spectroscopy, silver nanoparticles synthesized from N. sessilifolia and S. hydrangea had distinct absorption peaks at wavelengths of 407 to 424 nm and 414 to 415 nm, respectively. The crystalline nature of these synthetic silver nanoparticles was confirmed by XRD. FESEM analysis showed that the size of biosynthesized silver nanoparticles from N. sessilifolia and S. hydrangea extracts were 10-50 nm and 10-80 nm, respectively, and were cubic. The results of diffusion in agar showed that the largest diameter of the growth inhibition zone belonging to the synthetic silver nanoparticles from both extracts of N. sessilifolia (~ 26.00 mm) and S. hydrangea (~ 23.50 mm) was against Gram-positive bacteria Staphylococcus aureus. The most vigorous killing activity by synthetic silver nanoparticles from N. sessilifolia extract was against Klebsiella pneumoniae with a value of 250 μg/mL, two times stronger than rifampin. Conclusion Therefore, the studied extracts can be suitable options for fast and safe green synthesis of silver nanoparticles effective against some bacterial strains. These synthetic silver nanoparticles can be used as possible options and have strong potential for the production of natural antibiotics.